Sustainable innovative nanofibers containing Cobalt-MOF: a dual-action solution for microbial and chemical wastewater contamination - M. Alqahtani, Safar; Sur, Dharmesh; Altharawi, Ali; Roopashree, R.; Hussein Zwamel, Ahmed; Aldakhil, Taibah (Frontiers in Chemistry, 2025)
Today, wastewater treatment is essential and inevitable due to the water crisis caused by climate change and population growth. Although numerous methods and synthetic compounds have been successful in practical and laboratory applications, developing novel multifunctional compounds remains of interest to scientists. For this purpose, a new nanofiber containing Cobalt-MOF (metal-organic framework), polyvinyl alcohol (PVA), and polyvinyl pyrrolidone (PVP), which are known environmentally friendly polymers, was synthesized. After characterization and structure determination, the nanofiber was investigated for its ability to adsorb Congo Red dye and inhibit known microbial species in wastewater. This study showed that 91% of the 400 mg/L Congo red solution was absorbed by 0.06 g/L of the synthesized Cobalt-MOF/PVA-PVP Nanofibers at 1 h. Additionally, seven well-known strains (including Aeromonas hydrophila, Legionella pneumophila, Mycobacterium tuberculosis, Salmonella enterica, Pseudomonas aeruginosa, Escherichia coli, and Giardia lamblia) in wastewater were inhibited (with MIC of 8 μg/mL to 64 μg/mL) to the extent that some antibiotics could not affect them. This performance of the newly synthesized nanofiber can be attributed to its physical, chemical, and structural characteristics, such as compounds with biological properties present in its structure, as well as its high specific surface area. Therefore, researching and synthesizing similar compounds using the method presented in this study can lead to their development and application in wastewater treatment processes.